Targeted Collection of Plasmid DNA in Large and Growing Animal Muscles 6 Weeks after DNA Vaccination with and without Electroporation. (25th August 2015) - Dory, Daniel; Le Moigne, Vincent; Cariolet, Roland; Béven, Véronique; Keranflec'h, André; Jestin, André
Abstract : DNA vaccination has been developed in the last two decades in human and animal species as a promising alternative to conventional vaccination. It consists in the injection, in the muscle, for example, of plasmid DNA encoding the vaccinating polypeptide. Electroporation which forces the entrance of the plasmid DNA in cells at the injection point has been described as a powerful and promising strategy to enhance DNA vaccine efficacy. Due to the fact that the vaccine is composed of DNA, close attention on the fate of the plasmid DNA upon vaccination has to be taken into account, especially at the injection point. To perform such studies, the muscle injection point has to be precisely recovered and collected several weeks after injection. This is even more difficult for large and growing animals. A technique has been developed to localize precisely and collect efficiently the muscle injection points in growing piglets 6 weeks after DNA vaccination accompanied or not by electroporation. Electroporation did not significantly increase the level of remaining plasmids compared to nonelectroporated piglets, and, in all the cases, the levels were below the limit recommended by the FDA to research integration events of plasmid DNA into the host DNA.